Pengaruh konservatisme akuntansi, struktur modal dan arus kas bebas terhadap nilai perusahaan sebelum dan selama pandemi covid-19 pada perusahaan telekomunikasi yang terdaftar di bursa efek indonesia (BEI) - Patricia, Mayang; Rusmanto, Toto (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
This study aims to obtain empirical evidence about the effect of accounting conservatism, capital structure and free cash flow on firm value. The sample in this study is the quarterly financial statements of all telecommunication companies listed on the Indonesia Stock Exchange (IDX) in 2019-2021 before and during the Covid-19 outbreak. Data collected by purposive sampling method. The research was conducted using multiple linear regression analysis. The sample in this study was 60 samples. The results of this study indicate that accounting conservatism and capital structure have no significant effect on firm value before and during covid-19, free cash flow and firm size have a positive effect on firm value before and during covid-19.